2001
DOI: 10.1046/j.0014-2956.2001.02569.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ibuprofen and warfarin on the allosteric properties of haem–human serum albumin

Abstract: Haem binding to human serum albumin (HSA) endows the protein with peculiar spectroscopic properties. Here, the effect of ibuprofen and warfarin on the spectroscopic properties of ferric haem–human serum albumin (ferric HSA–haem) and of ferrous nitrosylated haem–human serum albumin (ferrous HSA–haem‐NO) is reported. Ferric HSA–haem is hexa‐coordinated, the haem‐iron atom being bonded to His105 and Tyr148. Upon drug binding to the warfarin primary site, the displacement of water molecules − buried in close proxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
143
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 125 publications
(168 citation statements)
references
References 33 publications
20
143
1
1
Order By: Relevance
“…Furthermore, this behavior, which underlies the occurrence of multiple conformations of iron(II) heme-HSA, may have great impact on the function of heme-HSA as a metabolite and drug transporter, since this proton-linked modulation is reflected in its capability of interacting with molecules circulating in the bloodstream, as previously demonstrated [3,8,20,22,[29][30][31][32]. Therefore, HSA, not only acting as a heme carrier but also displaying transient heme-based properties, represents a case for ''chronosteric effects'' [62], which opens the scenario toward the possibility of a time-and metabolite-dependent multiplicity of roles for HSA.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Furthermore, this behavior, which underlies the occurrence of multiple conformations of iron(II) heme-HSA, may have great impact on the function of heme-HSA as a metabolite and drug transporter, since this proton-linked modulation is reflected in its capability of interacting with molecules circulating in the bloodstream, as previously demonstrated [3,8,20,22,[29][30][31][32]. Therefore, HSA, not only acting as a heme carrier but also displaying transient heme-based properties, represents a case for ''chronosteric effects'' [62], which opens the scenario toward the possibility of a time-and metabolite-dependent multiplicity of roles for HSA.…”
Section: Discussionmentioning
confidence: 88%
“…According to Sudlow's nomenclature, bulky heterocyclic anions bind preferentially to Sudlow's site I (located in subdomain IIA), whereas Sudlow's site II (located in subdomain IIIA) is preferred by aromatic carboxylates with an extended conformation ( Fig. 1) [3,11,[18][19][20][21][22][23][24]. Among others, HSA is able to bind 7 equiv of long-chain fatty acids (FAs) at multiple binding sites (labeled FA1 to FA7) ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heme-HSA shows a considerably high r 1 value (approximately 25 s -1 mM -1 ), compared with other heme-proteins such as hemoglobin and myoglobin [11,19,32,[48][49][50][51]. Nuclear magnetic relaxation dispersion studies of heme-HSA revealed a strong paramagnetic contribution due to a cluster of water molecules buried near the heme that may be employed to follow a number of events including conformational transitions [16]. Addition of GnCl up to 5.0 M brings about a progressive decrease of r 1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One of the FA binding sites (FA1) has evolved to selectively bind heme with high affinity (K d = 1.0 9 10 -8 M [11]) with the tetrapyrrole ring arranged in a D-shaped cavity limited by Tyr138 and Tyr161 residues that provide p-p stacking interaction with the porphyrin and supply a donor oxygen (from Tyr161) for the Fe(III) heme iron [10][11][12][13][14]. In turn, heme binding to HSA endows the protein with heme-based reactivity [4,15] and spectroscopic properties [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%